2015
DOI: 10.1111/cen.12951
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of TSP‐1, NF‐κB and TGF‐β1 in polycystic ovarian syndrome (PCOS) patients in northern China suggest PCOS is associated with chronic inflammation

Abstract: These results support the association between PCOS and chronic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 32 publications
2
40
0
Order By: Relevance
“…The MAPK/ERK/p38 signaling pathway contributes to the regulation of inflammation and cytokine production 60,61 , and the dysregulation of inflammation-related molecules is associated with PCOS conditions [52][53][54]62 . Furthermore, like the activation of NFκB signaling that induces the transcriptional levels of inflammation-related gene expression in ovarian granulosa cells and in serum in PCOS patients 51,63 , our previous study has shown that the sustained metformin treatment markedly suppresses uterine inflammatory gene expression, especially the Il-6 and TNFα mRNAs that are associated with inhibition of nuclear NFκB translocation in PCOS-like rats 28 . Importantly, p38 can antagonize ERK1/2 signaling mediated by protein phosphatase 2A and consequently down-regulate inflammatory cytokine and chemokine production 61 , and the anti-inflammatory effects of MAPK/p38 are involved in the regulation of NFκB activity 60 .…”
Section: Commentmentioning
confidence: 96%
See 1 more Smart Citation
“…The MAPK/ERK/p38 signaling pathway contributes to the regulation of inflammation and cytokine production 60,61 , and the dysregulation of inflammation-related molecules is associated with PCOS conditions [52][53][54]62 . Furthermore, like the activation of NFκB signaling that induces the transcriptional levels of inflammation-related gene expression in ovarian granulosa cells and in serum in PCOS patients 51,63 , our previous study has shown that the sustained metformin treatment markedly suppresses uterine inflammatory gene expression, especially the Il-6 and TNFα mRNAs that are associated with inhibition of nuclear NFκB translocation in PCOS-like rats 28 . Importantly, p38 can antagonize ERK1/2 signaling mediated by protein phosphatase 2A and consequently down-regulate inflammatory cytokine and chemokine production 61 , and the anti-inflammatory effects of MAPK/p38 are involved in the regulation of NFκB activity 60 .…”
Section: Commentmentioning
confidence: 96%
“…Importantly, chronic inflammation has been shown to be closely correlated to high inflammatory mediator production under PCOS conditions 2 . For example, there is a noticeable increase in the inflammatory cytokines such as IL-6 and TNFα in the peripheral circulation of PCOS patients 50,51 . Similarly, several studies by our laboratory and others have described increased gene expression of IL-6, TNFα, and Mcp-1 (CCL-2) in PCOS patient endometrium and the PCOS-like rat uterus 10,28,[52][53][54] .…”
Section: Commentmentioning
confidence: 99%
“…During the past two decades, emerging evidence has supported the essential contribution of AGE-RAGE to increased oxidative stress and inflammation. These processes perturbate the ovarian microenvironment and may cause infertility [2]. According to Merhiet et al [11], high follicular fluid sRAGE correlates with elevated ovarian reserve as measured by AMH [19].…”
Section: Discussionmentioning
confidence: 99%
“…PCOS is characterized by hyper-androgenism, polycystic ovaries, oligoovulation, and chronic anovulation [1]. Although the etiology of PCOS is unknown, imbalances between proinflammatory and anti-inflammatory pathways play a role in the pathogenesis of PCOS [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor kappaB (NF-κB) is a crucial factor regulating in ammation, and following exogenous stimulation-free NF-κB translocates into the nucleus where it induces gene transcription to regulate and promote an in ammatory reaction [31]. It is reported that NF-κB in the PCOS groups weas signi cantly higher [32], indicating that PCOS maight be associated with chronic in ammation. In addition, GO classi cation also pointed to in ammatory response, upholding its importance in PCOS.…”
Section: Topological Characteristics Of Pclmn and The Cellular Localimentioning
confidence: 99%